A Simplified Step-by-Step Decoding Algorithm for Parallel Decoding of Reed-Solomon Codes - Liu, Xiaobei; Lu, Chao; Cheng, Tee Hiang; Koh, Soo Ngee (IEEE transactions on communications, 2007)
A simplified parallel step-by-step decoding algorithm is proposed for decoding Reed-Solomon (RS) codes. It uses new method to calculate the determinants of the temporarily changed syndrome matrices, based on the property of these matrices determined in this paper. By using the proposed method, the calculations of the determinants of the temporarily changed syndrome matrices become much simpler and thus the computational complexity of the step-by-step decoding algorithm is significantly reduced.